Evaluating Technology (Social Media and Apps) And Blockchain for Cost- Savings and Efficiencies in Event Management - Rakesh, Sarpal; Tamil Selvi, Renganathan; Rachel Low, Ti Yin (INTI International University, 2024)
This literature review investigates the transformative impact of technology, particularly social media, event-mobile apps, and blockchain on the event management industry. This exploration of technology's influence on the industry reveals a profound shift in how events are planned, marketed, and executed. It addresses two key research questions: the influence of apps and social media on cost savings in event marketing and how blockchain technology enhances efficiencies, specifically in ticketing and data security. Social media is shown to be a cost-effective marketing tool that reduces expenses, though it comes with its own set of challenges, such as data management and maintaining visibility in a crowded digital landscape. Event-mobile apps are highlighted for their ability to reduce costs, streamline logistics, and improve attendee experiences, but they face obstacles related to user adoption and potential obsolescence. This review also delves into how blockchain technology revolutionizes the industry by addressing issues like ticket fraud and manipulation through transparent and immutable transaction records. However, it introduces concerns about data privacy and visibility. In summary, technology is reshaping the event management landscape, offering cost reduction and operational efficiency, while simultaneously presenting ongoing challenges and opportunities for innovation.